The Influence of Intrinsic Motivation and Organizational Citizenship Behavior (OCB) on the Performance of Soldiers in Detachment Equipment XIV/3 Kendari/Paldam XIV/Hasanuddin/Kodam XIV/Hasanuddin - Muh. Saiful; Rahmat Majid; Abdul Razak (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
National defense is a crucial aspect of maintaining the sovereignty and security of a nation. This study focuses on the influence of intrinsic motivation and Organizational Citizenship Behavior (OCB) on the performance of soldiers in Detachment Equipment XIV/3 Kendari. There is a lack of in-depth research on the impact of these two factors in a military context. The research method used is a survey with questionnaires and data analysis using multiple linear regression. The results show that intrinsic motivation has a significant positive influence on soldier performance. Additionally, OCB also has a significant positive influence on performance. The interaction between intrinsic motivation and OCB leads to greater performance improvement. These findings indicate that a comprehensive human resource development strategy, which includes enhancing intrinsic motivation and encouraging OCB behavior, is crucial for achieving optimal performance in a military environment. The practical implications of these findings are that developing effective policies and training programs should be a priority to improve soldier performance